An Environmental Scan of the Role of Nurses in Preventing Fetal Alcohol Spectrum Disorders. (1st February 2018) - Mitchell, Ann M.; King, Diane K.; Kameg, Brayden; Hagle, Holly; Lindsay, Dawn; Hanson, Bridget L.; Kane, Irene; Puskar, Kathy; Albrecht, Susan; Shaputnic, Carolyn; Porter, Becky R.; Edwards, Alexandra E.; et al.
ABSTRACT: Nurses are in an ideal position to talk to their patients of reproductive age about alcohol use and encourage the prevention of alcohol-exposed pregnancies. Effective conversations can be efficiently included in the clinical encounter to identify alcohol misuse and offer appropriate follow-up. This report presents results of an environmental scan of resources relevant to nursing professionals and nurses' role in addressing alcohol misuse. Gaps in nursing education and practice guidelines with regard to defining the nursing role in preventing alcohol-exposed pregnancies were revealed. Findings identified a need to promote adoption among nurses of evidence-based preventive practices to prevent alcohol misuse.